2011
DOI: 10.1007/s10704-011-9613-y
|View full text |Cite
|
Sign up to set email alerts
|

Generalised stress intensity factors for rounded notches in plates under in-plane shear loading

Abstract: The Notch Stress Intensity Factors (NSIFs) quantify the intensities of the asymptotic linear elastic stress distributions of sharp (zero radius) V-shaped notches. When the notch tip radius is different from zero, the singular sharp-notch field diverges from the rounded-notch solution in the close neighborhood of the notch tip. Nevertheless the NSIFs might continue to be parameters governing fracture if the notch root radius is small enough. Otherwise they can be seen simply as stress field parameters useful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 63 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…This is the hypothesis implicitly used by Neuber without the explicit introduction of the stress intensity factors [1], but is approximately true only when the fictitiously enlarged notch root radius is sufficiently small. In the reality, for large  f , K 1 and K 2 do not match K 1 and K 2 [20,34].…”
Section: Conditionsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is the hypothesis implicitly used by Neuber without the explicit introduction of the stress intensity factors [1], but is approximately true only when the fictitiously enlarged notch root radius is sufficiently small. In the reality, for large  f , K 1 and K 2 do not match K 1 and K 2 [20,34].…”
Section: Conditionsmentioning
confidence: 96%
“…Other sets of equations [32,33] applicable to rounded V-notches of different shape do not have this property as discussed in Ref. [34]. In that paper it was also documented the stable trend of the generalized notch stress intensity factors given in Eqs (4) and (8) as a function of the distance r. The problem of the oscillating trend of Kand K  described in [33] for blunt V-notches with flanks tangent to the notch root radius is overcome by employing the set of equations reported in [21].…”
Section: Conditionsmentioning
confidence: 99%
“…The accuracy of the stress fields suggested has been verified by using the finite element (FE) analyses, and very good agreement has been shown. In the other paper published by Lazzarin et al [59], they investigated the notch stress intensity factors (NSIFs) for blunt notches, a part of which has been concentrated on VO-notches under mode II loading. In a study reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the opening angles of notch specimen ranges from 0 degree to 180 degrees. In previous studies, most cases mainly concentrated on the crack initiation, 5,6) crack propagation rate and fracture toughness, 7,8) the shape of notch and the radius of notch tip, 9,10) the stress intensity factor and its distribution of notch tip 11,12) by the tension or three-point bending (TPB) or four-point bending (FPB).…”
Section: Introductionmentioning
confidence: 99%